Feminist stylistic analysis and LGBTQA+ representation in Lady Gaga’s born this way - Rahmadsyah Rangkuti; Siti Hafifah (Universitas Bengkulu, 2022)
This study is intended to find out the exact meaning of the lyrics at different levels of language, and phonetic devices, as well as to reveal how these stylistic devices work on Lady Gaga’s Born This Way (LGBTQA+). This study employed qualitative content analysis. The source of the data was the song Born This Way by Lady Gaga and the data were the linguistics aspects of the song, which are the words, phrases, clauses and sentences, as well as the discourse unit of the song. It was found that the song aims to speak to as many perspectives as possible, through different races, sexualities, and gender expressions, through the language uses that are represented in the song. By then, this song has completely succeeded to not only raising up feminist voice, but also, most likely, if there was no song with all the impact and events, understanding about gender and equality would not develop as it is today. The song strongly emphasizes the equality notion by accepting who we are as we are all born this way. The choices of word, phrase, clause and sentence as well as the discourse unit credit about self-liberation, and loving every part of oneself, no matter what race, belief, or sexuality one is on. This also proves that this song is not solely an LGBTQA+ community anthem, instead, it is a song for all kind of self-acceptance.